PENGARUH PEMBERIAN STABILIZATION EXERCISE TERHADAP KEMAMPUAN FUNGSIONAL NYERI SENDI BAHU - Vicha Albanie Sasalbela; Yulianto Wahyono; Aditya Johan R (Jurnal Nasional Fisioterapi, 2024)
Background: The shoulder joint or glenohumeral articulation is a ball and socked joint arrangement. This joint moves very widely and is mobile so it is relatively easy to get injured, some injuries to the shoulder joint include tendinitis, bursitis, capculitis and thoracic outlet syndrome (TOS). Some of these injuries will result in shoulder joint pain. The reported prevalence of shoulder pain ranges from 2.4% - 26% in the world. To treat shoulder pain, you can use stabilization exercises, glenohumeral rotation, various movements in the shoulder joint have a big risk of impacting on stabilization disorders in the shoulder joint and shoulder joint pain with stabilization can restore stability to the shoulder joint. Objective: To determine the effect of providing stabilization exercise on increasing functional ability in conditions of shoulder joint pain. Method: This study used one group with control where 30 subjects were divided into a treatment group that was given stabilization exercise consisting of 15 people and a control group that was not given any treatment consisting of 15 people. This research was conducted in August 2023. Shoulder joint pain was measured using SPADI, measurements were taken before and after treatment. Results: Based on the results of statistical tests before and after treatment in the treatment group, the result was p = 0,001 (p<0.05), which means there is a different effect. To prove that these results really had an effect because of the treatment, a post-post difference test was carried out between groups, which resulted in p = 0,006 (p<0.05), which means there was a difference in effect. Conclusion: The research "The Effect of Stabilization Exercise on Functional Ability for Shoulder Joint Pain" has an effect on the functional ability for shoulder joint pain.